Katarzyna Barbara Kochan, Edukacja elementarna i elementarze porozbiorowe w II Rzeczypospolitej, Kraków 2009, ss. 96. - Gulczyńska, Justyna (Biuletyn Historii Wychowania, 2009)
Katarzyna Barbara Kochan, Edukacja elementarna i elementarze porozbiorowe w II Rzeczypospolitej, Kraków 2009, ss. 96.